Human monocyte-derived macrophages inhibit HCMV spread independent of classical antiviral cytokines. Issue 1 (31st December 2018) - Becker, Jennifer; Kinast, Volker; Döring, Marius; Lipps, Christoph; Duran, Veronica; Spanier, Julia; Tegtmeyer, Pia-Katharina; Wirth, Dagmar; Cicin-Sain, Luka; Alcamí, Antonio; Kalinke, Ulrich
ABSTRACT: Infection of healthy individuals with human cytomegalovirus (HCMV) is usually unnoticed and results in life-long latency, whereas HCMV reactivation as well as infection of newborns or immunocompromised patients can cause life-threatening disease. To better understand HCMV pathogenesis we studied mechanisms that restrict HCMV spread. We discovered that HCMV-infected cells can directly trigger plasmacytoid dendritic cells (pDC) to mount antiviral type I interferon (IFN-I) responses, even in the absence of cell-free virus. In contrast, monocyte-derived cells only expressed IFN-I when stimulated by cell-free HCMV, or upon encounter of HCMV-infected cells that already produced cell-free virus. Nevertheless, also in the absence of cell-free virus, i.e., upon co-culture of infected epithelial/endothelial cells and monocyte-derived macrophages (moMΦ) or dendritic cells (moDC), antiviral responses were induced that limited HCMV spread. The induction of this antiviral effect was dependent on cell-cell contact, whereas cell-free supernatants from co-culture experiments also inhibited virus spread, implying that soluble factors were critically needed. Interestingly, the antiviral effect was independent of IFN-γ, TNF-α, and IFN-I as indicated by cytokine inhibition experiments using neutralizing antibodies or the vaccinia virus-derived soluble IFN-I binding protein B18R, which traps human IFN-α and IFN-β. In conclusion, our results indicate that human macrophages and dendritic cells can limit HCMV spread by IFN-I dependent as well as independent mechanisms, whereas the latter ones might be particularly relevant for the restriction of HCMV transmission via cell-to-cell spread.